2016
DOI: 10.1016/j.cmet.2016.06.016
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Gut Microbiota Manipulation by Antibiotics on Host Metabolism in Obese Humans: A Randomized Double-Blind Placebo-Controlled Trial

Abstract: Highlights d Vancomycin but not amoxicillin treatment alters human gut microbiota composition d Vancomycin treatment alters short-chain fatty acid and bile acid concentrations d Modulation of adult microbiota by 7-day antibiotics does not affect host metabolism d Host metabolism remained unchanged at 8-week follow-up, despite deviant microbiota

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
205
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 292 publications
(233 citation statements)
references
References 62 publications
15
205
4
3
Order By: Relevance
“…We demonstrated that oral administration of VANCO or AMOX for 7 days has no major effect on ex vivo β-adrenergic sensitivity in adipocytes derived from obese insulin resistant men. We have previously reported that VANCO but not AMOX treatment markedly reduced microbiota diversity and altered its composition, predominantly by decreasing gram-positive Firmicutes [19]. In the current sub-cohort, microbiota changes were comparable (data not shown).…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…We demonstrated that oral administration of VANCO or AMOX for 7 days has no major effect on ex vivo β-adrenergic sensitivity in adipocytes derived from obese insulin resistant men. We have previously reported that VANCO but not AMOX treatment markedly reduced microbiota diversity and altered its composition, predominantly by decreasing gram-positive Firmicutes [19]. In the current sub-cohort, microbiota changes were comparable (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…In the current sub-cohort, microbiota changes were comparable (data not shown). VANCO treatment for 7 days decreased the abundance of Clostridium clusters XIVa and IV, which was accompanied by a reduced conversion of primary to secondary BAs, and a lower concentration of fecal SCFA [19]. Interestingly, SCFA and BA receptors (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations